The use of seismostratigraphy for exploration of Miocene gas-bearing reservoir facies in the NE part of the Carpathian Foreland Basin (Poland) - PIETSCH, Kaja; PORĘBSKI, Szczepan J.; MARZEC, Paweł (Geology, Geophysics and Environment, 2010)
Sedimentological and seismostratigraphic interpretation of a dip cross-section located in the northwestern part of the Wielkie Oczy Graben, across the Markowice - Lubliniec elevation and farther to the NE resulted in the identification of the base-Sarmatian angular unconformity (UNO) and allowed to subdivide the Machów Formation into seven genetic sequences composed mainly of deltaic deposits. The unconformity reflects extension episode superimposed on regional south-westward rotation of the basin floor and is overstepped and upplapped towards the NE by deltaic bodies fed from an southerly (orogenic) source. The upplaping pinchouts may form combined, structural-stratigraphic traps for methane generated in delta front-prodelta heteroliths. Unconformity UNO is farther to the SE overlain locally by gas-bearing massive sandstones of intrabasinal or northerly provenience, and similar sandstones may be expected to occur in the study area below the belt of upplapping pinch-outs.